2018
DOI: 10.15403/jgld.2014.1121.273.hey
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokines Profile in Treated Celiac Disease Compared with Non-celiac Gluten Sensitivity and Control: a Marker for Differentiation

Abstract: Inflammatory cytokines are implicated in the pathogenesis of CD, and their serum levels might help to identify a diagnostic marker to differentiate CD from NCGS. However, further studies with a larger sample size are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
(52 reference statements)
2
11
0
1
Order By: Relevance
“…Bernardo et al [25] also obtained the same result after the evaluation of 42 CD patients and 24 healthy individuals in a gastroenterology clinic for intestinal pathologies. However, IL-15 did not increase in NCGS group [7] . In our study, the diagnostic power of the IL-15 was evaluated and indicated that it is not an efficient tool for detecting CD (sensitivity = 57.30%) in the NCGS group.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Bernardo et al [25] also obtained the same result after the evaluation of 42 CD patients and 24 healthy individuals in a gastroenterology clinic for intestinal pathologies. However, IL-15 did not increase in NCGS group [7] . In our study, the diagnostic power of the IL-15 was evaluated and indicated that it is not an efficient tool for detecting CD (sensitivity = 57.30%) in the NCGS group.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, more than 68.79 ng/ml of this cytokine could be considered as an evidence of CD by comparing it with the healthy control group. Heydari et al [7] and Di Sabatini et al [24] reported that the serum IL-1α and IL-1β levels were not significantly different among CD, NCGS, and healthy control groups. In contrast, Manavalan et al [5] showed a high level of IL-1β in CD patients compared to the control group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These ndings have been previously reported in sera. In fact, to our knowledge, this is the rst depiction of cytokine production on duodenal mucosa from NCSRGS patients by immunohistochemistry, since other studies have evaluated cytokine levels on serum and peripheral blood mononuclear cells or duodenal mucosa culture supernatants by ELISA (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 98%